Use of Visual Media in Health Promotion About Immunization - Prita Devy Igiany (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Implementation of health promotion needs to be addressed is the selection of media y ang accordance with the target. Health promotion media is a tool used to help the health promotion process. The right media make information more easily accepted by the target, so that behavior will also change according to the knowledge gained. The purpose of this study is to determine the effect of using visual media (leaflets) in health promotion about immunization. This research is a pre-experimental study with One Group Pretest-Posttest Design. The data analysis technique used univariate and bivariate analysis. Univariate analysis was performed to see responden characterstic, while while bivariate data analysis was performed using the Wilcoxon test to see how visual media's effect to knowledge and behaviour of immunization. The result showed that health promotion using visual media, namely leaflets can significantly increase both the knowledge and behavior of mothers about immunization